Can Sex Education Delay Early Sexual Debut?. (May 2013) - Erkut, Sumru; Grossman, Jennifer M.; Frye, Alice A.; Ceder, Ineke; Charmaraman, Linda; Tracy, Allison J.
In this study, we examine whether a nine-lesson sex education intervention, " Get Real: Comprehensive Sex Education That Works, " implemented in sixth grade, can reduce the number of adolescents who might otherwise become "early starters" of sexual activity (defined as heterosexual intercourse) by seventh grade. Participants were 548 boys and 675 girls who completed surveys in both sixth grade (baseline) and seventh grade (follow-up). The sample was 35% Latino, 32% Black, 24% White, 3% Asian, and 6% biracial. Students randomly assigned to the control condition were 30% more likely to initiate sex by follow-up when controlling for having had sex by sixth grade, demographic variables, and a tendency to give socially desirable responses. This finding is noteworthy because previous research has identified early starters to be prone to poor outcomes in sexual health, family formation, economic security, and incarceration and few middle school interventions have shown an effect on behavioral outcomes.